2021
DOI: 10.3390/ijms222413634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Osthole on Inflammatory Gene Expression and Cytokine Secretion in Histamine-Induced Inflammation in the Caco-2 Cell Line

Abstract: Hyperactivity of the immune system in the gastrointestinal tract leads to the development of chronic, inflammation-associated disorders. Such diseases, including inflammatory bowel disease, are not completely curable, but the specific line of treatment may reduce its symptoms. However, the response to treatment varies among patients, creating a necessity to uncover the pathophysiological basis of immune-mediated diseases and apply novel therapeutic strategies. The present study describes the anti-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“… 65 A similar relationship to this manuscript was found in the studies of Kordulewska et al, where OST decreased H4R expression in the Caco-2 line at each concentration tested. 35 Surprisingly, we found that H4R expression was higher under the influence of LPS than under that of histamine. The answer to these differences could be the fact that the skin of people with AD faces constant fluctuations and higher concentrations of histamine, which can desensitize the receptor to histamine even in vitro.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“… 65 A similar relationship to this manuscript was found in the studies of Kordulewska et al, where OST decreased H4R expression in the Caco-2 line at each concentration tested. 35 Surprisingly, we found that H4R expression was higher under the influence of LPS than under that of histamine. The answer to these differences could be the fact that the skin of people with AD faces constant fluctuations and higher concentrations of histamine, which can desensitize the receptor to histamine even in vitro.…”
Section: Discussionmentioning
confidence: 69%
“…Osthole (OST) (7-methoxy-8-(3-methyl-2-butenyl)-2H-1-benzopyran-2-one) is a natural coumarin and a major chemical constituent of the plant Cnidium monnieri (L) Cusson and is considered a promising natural product that could be used pharmacologically in the future. These include anti-cancer [24][25][26] anti-inflammatory, [27][28][29][30] antioxidant, 31 anti-angiogenic, 32 anti-allergic 27,33,34 immunomodulatory 33,35 and hepatoprotective [36][37][38] activities. In our previous publications, we found that OST is immunosuppressive in peripheral blood mononuclear cells (PBMCs) isolated from children with allergies or asthma 27,30,[39][40][41][42][43] and autism spectrum disorders (ASD), in keratinocytes and fibroblast cell lines 28, and in a 3D skin model.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in animal models of colitis, isoliquiritigenin, paeoniflorin, resveratrol, quercetin, shikonin, piperine, imperatorin, roxithromycin, α‐linolenic acid, genistein and osthole independently exert anti‐inflammatory activity, typically via NF‐κB inhibition or a reduction in pro‐inflammatory cytokine secretion (i.e. TNF‐α, interleukin‐6, interleukin‐1β, interleukin‐8) (Abron et al, 2018; Andújar et al, 2012; Choi et al, 2015, 2016; Cui et al, 2010; Gu et al, 2017; Guo et al, 2020; Kordulewska et al, 2021; Luo & Luo, 2021; Reifen et al, 2015; Sotnikova et al, 2013). Interestingly, each of these substances has an inhibitory effect on MRGPRX2‐mediated mast cell degranulation (Callahan et al, 2020; Ding et al, 2021; Hou et al, 2018; Kumar et al, 2020; Ogasawara & Noguchi, 2021; Qiao et al, 2020; Wang, Wang, et al, 2021a; Wang, Zhang, et al, 2021b; Wang, Zhang, Li, et al, 2020b; Wang, Zhang, Wang, et al, 2020a; Zhang et al, 2020).…”
Section: Mrgprs In Mast‐cell Induced Gastrointestinal Inflammationmentioning
confidence: 99%
“… 9 Our previous studies also demonstrated several natural compounds, such as sarsasapogenin, 5 shikonin, 10 and celastrol, 11 that served as potential anti‐RA drugs. Osthole (OS) is an active ingredient that could be extracted from Cnidium , Angelica , and Citrus plants with low cost and presented anti‐inflammatory 12 , 13 , 14 and immunosuppressive activities 15 , 16 in human diseases. Nevertheless, the therapeutical effect of OS on RA and RA‐ILD is not fully understood, and the potential role of OS in improving the sensitivity of traditional anti‐RA drugs is yet to be explored.…”
Section: Introductionmentioning
confidence: 99%